Website Sebagai Sarana Administrasi dan Pemesanan Produk atau Jasa pada Klinik Kencantikan XYZ - Nababan, Yerika Mekarsena; Sevani, Nina (Teknik dan Ilmu Komputer, 2014)
Beauty clinik Is a well growing type of clinic today. This kind clinic offers beauty treatment service and sells beauty products. Some clinic still use manual process to handdle their administrasion and selling process. This process used paper and filing cabinet to store and process data. This condition can create some troubles related storing and searching for information. The presence of a website intergrated with a database to manage the customers data can upgrade the efficiency and effectiveness of the administration process in the clinic. The website coverage also can also increase the services to offer to customers, by allowing online reservation and consultation. To secure the data, this website divides its users into some group based on their acces privileges. The development of this web underwent some steps, starting from observations and interviews, followed by the design step (database, data flow, hierarchical menu), and ended by testing using white box and black box method.ÃÂ Keywords : website, administration, booking, beauty clinic